Filtering of Background Variation Factors in Stream Sediment Geochemical Surveys Application to Zn Sedex Deposits in the Gatineau Area, Southwestern Quebec, Canada (1efe4fef-ee6d-45e5-a4d6-e70ef72ac68a) - Claude Bellehumeur; Michel Jebrak (Canadian Institute of Mining, Metallurgy and Petroleum, 1993)
Regional and orientation geochemical stream sediment surveys were carried out by the Quebec Department of Energy and Resources in southwestern Quebec, over a part of the Mont Laurier Terrane of the Grenville Province. The area contains some small stratiform zinc deposits. The response of Zn mineralization to geochemical surveys is weak; the known mineralization is not dermed by anomalous samples and consistent patterns. This study uses a technique that increases the geochemical signature of Zn mineralization in filtering out geochemical background components related to lithologies and surficial conditions. The background variations were modelled using principal component analysis, and the filtering technique consists of the partial reconstruction of the data matrix from results of principal component analysis. The filtering procedure considerably enhances the Zn anomalies located in the catchment basins of Zn deposits, and defines some new anomalies in proximity to the marbles of the Mont-Laurier Terrane, the principal metallotect of Zn mineralization.